Efficacy of Asymmetric Myopic Peripheral Defocus Lenses in Spanish Children: 24-Month Randomized Clinical Trial Results - Clara Martinez-Perez; Miguel Ángel Sánchez-Tena; Jose Miguel Cleva; Cesar Villa-Collar; Marta Álvarez; Eva Chamorro; Cristina Alvarez-Peregrina (Children)
Background/Objectives: Asymmetric myopic peripheral defocus lenses (MPDLs) have proven to be effective in slowing the progression of myopia in Spanish children over a period of 12 months. The purpose of this study was to assess the MPDL spectacles’ efficacy in slowing myopia progression over a 24-month period in children. Methods: This study extends the follow-up period of the double-masked, prospective, and randomized clinical trial previously published to 24 months. Children from 6 to 12 years were assigned to two groups: a control group wearing spherotorical single vision lenses (SVLs) or a treatment group wearing MPDL lenses. Inclusion criteria included children with myopia less than −0.50 D, astigmatism below 1.50 D, and best-corrected visual acuity of at least 20/20. Participants underwent cycloplegic autorefractive examination and axial length (AL) measurements at the baseline and six and twelve months in the study already published, and twenty-four months later in the present study. Lifestyle factors, including outdoor activities and digital device use, were also assessed. Baseline characteristics, including age, refractive error, and AL, were comparable between groups. Dropout rates were 15.9%, with 14 participants lost to follow-up, distributed equally between the two groups. Results: After 24 months of follow-up, 69 children remained in this study, comprising 34 participants in the SVL cohort and 35 in the MPDL cohort. Over 24 months, the MPDL group showed significantly less AL elongation than the SVL group (0.27 ± 0.23 mm and 0.37 ± 0.24 mm; p = 0.0341). The mean relative AL increase was 1.10 ± 0.95% in the MPDL group, compared to 1.56 ± 1.02% in the SVL group (p = 0.0322). Younger children exhibited faster AL growth, while digital device use and outdoor activities did not affect AL changes. Conclusions: MPDL spectacle lenses substantially slowed myopia progression over a 24-month period, with 28.7% less progression in absolute AL growth and 29.8% in relative AL growth compared to SVL. These results indicate that MPDL lenses are an effective method for slowing myopia progression.